An Update on Taxation in China - Miller, Jonathan (Columbia Journal of Asian Law, 1987)
On April 12, 1986, the central government of the People’s Republic of China issued a new five year plan reaffirming the country’s commitment to economic decentralization. The PRC announced a plan to broaden the role of free market forces and to curtail the interdependence of commercial enterprise and the state. This plan demonstrates China’s current quest to make more varied and efficient use of capital investment. U.S. investors may wish to consider the effects of the new plan on doing business in China. This note examines specific features of China’s tax system to aid the U.S. investor in planning under the present tax system and in predicting future developments. To the extent that a tax system reflects national economic policy, it is necessary to evaluate the Chinese tax system not only on its own terms but also in light of China’s experimentation with profit-motivated business and investment. This discussion takes up three aspects of tax planning in China: first, an overview of the present tax scheme; second, the influence of that tax scheme on whether and how to do business in China; and third, the interaction between Chinese tax incentives and U.S. tax law. A summary of PRC income taxes is provided in the chart following the text.